UNDERSTANDING THE PROBLEM OF HADITH NARRATION: TOWARDS A COMPREHENSIVE READING OF HADITH - M. Nur, Maizuddin (UIN Ar-Raniry, 2015)
As the source of Islamic teaching, hadith must be apprehended according to the intent of the prophet. If done otherwise, the understanding of prophet’s intention as the explanation of Quranic teaching can be misunderstood. The chance becomes even more likely as hadith has its own problems, especially in the context of its comprehension. These problems will create conclusions which at times influence ones’ understanding. Among the problems are the complete narration of the hadith, riwayat bi al-ma’na, and conciseness of the hadith. Ones’ understanding of a hadith whose information is complete would be different from the one that is not. Thus, the understanding of hadith problems is very crucial to comprehensively understand hadith.